Spatial databases : - Rigaux, Philippe (Morgan Kaufmann Publishers, 2002)
Spatial Databases covers all of the major themes of the field -- representation,query languages, computational geometry, spatial indexing -- using geographic information systems as the principal application domain and motivation. It will make an excellent introduction for computer science professionals and students interested in exploring GIS, or for GIS professionals interested in learning more about the computer science foundations of the field. The book is also an excellent guide to the literature, with comprehensive bibliographic notes at the end of each chapter